2022
DOI: 10.1093/ajcn/nqac278
|View full text |Cite
|
Sign up to set email alerts
|

The association between TMAO, CMPF, and clinical outcomes in advanced chronic kidney disease: results from the European QUALity (EQUAL) Study

Abstract: Background Trimethylamine N-oxide (TMAO), a metabolite from red meat and fish consumption, plays a role in promoting cardiovascular events. However, data regarding TMAO and its impact on clinical outcomes are inconclusive, possibly due to its undetermined dietary source. Objective We hypothesized circulating TMAO derived from fish intake might cause less harm compared to red meat source by examining the concomitant level of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The gut microbiota and their metabolism and effect on the intestinal barrier function are an interesting target as they are at the origin of toxin generation and especially of those uremic toxins that have been associated with worse overall and cardiovascular outcome in CKD. 10,11 To develop a systems biology view of gut-heart-kidney interactions, we apply the conceptual framework of the remote sensing and signaling theory. This theory focuses on remote small-molecule communication across inter-organ axes (eg, gut-brain, gut-heart-kidney, and gut-liver-kidney).…”
Section: Compendium On Increased Risk Of Cardiovascular Complications...mentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota and their metabolism and effect on the intestinal barrier function are an interesting target as they are at the origin of toxin generation and especially of those uremic toxins that have been associated with worse overall and cardiovascular outcome in CKD. 10,11 To develop a systems biology view of gut-heart-kidney interactions, we apply the conceptual framework of the remote sensing and signaling theory. This theory focuses on remote small-molecule communication across inter-organ axes (eg, gut-brain, gut-heart-kidney, and gut-liver-kidney).…”
Section: Compendium On Increased Risk Of Cardiovascular Complications...mentioning
confidence: 99%
“…The gut microbiota and their metabolism and effect on the intestinal barrier function are an interesting target as they are at the origin of toxin generation and especially of those uremic toxins that have been associated with worse overall and cardiovascular outcome in CKD. 10,11…”
mentioning
confidence: 99%
“…[19] A prospective study of 824 older patients with CKD stage 4 recruited from the European QUALity Study (EQUAL Study) showed that high TMAO levels in combination with low levels of 3-carboxy-4-methyl-5-propyl-2-furanpropionate (CMPF), a metabolite of furan fatty acids that reflect the intake of fish, were independently associated with an increased risk of all-cause mortality and shorter time until the start of renal replacement therapy. [20] When interpreting these data, the reduced renal excretion of TMAO [13] and the observation that loop diuretics [21] decrease the renal elimination rate of TMAO must be considered. Thus, patients with CKD and/or on loop diuretics may be more susceptible to a regular intake of deep-sea fish with high muscular TMAO content.…”
Section: Doi: 101002/mnfr202200859mentioning
confidence: 99%
“…The above phenomena are possibly due to overlapping risk factors among patients with ischemic stroke. Patients with cardioembolic stroke also suffer from hypertension (26), diabetes (27,28), renal insufficiency (29)(30)(31), and coronary artery disease (32), disorders that can all lead to elevated plasma TMAO concentrations, resulting in smaller differences in plasma TMAO levels among stroke patients with different etiologies. Xu et al (33) found drastically higher plasma TMAO levels in stroke patients in the LAA group and CE (Cardioembolic) group than in the control group, speculatively pointing to TMAO as crucial to the pathophysiology of atherosclerosisrelated stroke and suggesting that the increase in TMAO levels in the CE group was probably associated with the ability of TMAO to promote platelet hyperresponsiveness and heighten the risk of thrombosis (34).…”
Section: Tmao and The Subtypes Of Ischemic Strokementioning
confidence: 99%